Sequence of human haptoglobin cDNA: evidence that the alpha and beta subunits are coded by the same mRNA. - Raugei, G (1983)
We have isolated and sequenced a cDNA clone coding for human haptoglobin. Our sequence shows that haptoglobin is very likely synthesized as a single polypeptide chain which is then cleaved at an Arg residue to generate its two characteristic alpha and beta subunit. Southern blot analysis suggests that there are at least two copies of the haptoglobin gene per haploid genome.